9y-2z-12y+7z=

Simple and best practice solution for 9y-2z-12y+7z= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9y-2z-12y+7z= equation:


Simplifying
9y + -2z + -12y + 7z = 0

Reorder the terms:
9y + -12y + -2z + 7z = 0

Combine like terms: 9y + -12y = -3y
-3y + -2z + 7z = 0

Combine like terms: -2z + 7z = 5z
-3y + 5z = 0

Solving
-3y + 5z = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5z' to each side of the equation.
-3y + 5z + -5z = 0 + -5z

Combine like terms: 5z + -5z = 0
-3y + 0 = 0 + -5z
-3y = 0 + -5z
Remove the zero:
-3y = -5z

Divide each side by '-3'.
y = 1.666666667z

Simplifying
y = 1.666666667z

See similar equations:

| 4t-5t-12t= | | -10y-9y= | | 4x^2+5=59 | | .8x-.4x+.1x=5 | | 10x+11x= | | 12a-4= | | x^2-6x-57=0 | | x^6-7x^5-4x^4= | | 2x-8=3x+7 | | 12x-(8x-2)=10 | | 5x-4=96 | | -2(4x-5)=-70 | | x^2+92x-9=-100 | | 2(-2x+2)=-36 | | 4x+9+3x+3=33 | | -4(6x-10)=-32 | | 2(5x-4)-5x= | | x/7=6 | | 11x^2-5x-46=0 | | 13y+6=12y+16 | | 2+1/2=1+1/4(x-2) | | 312=16t^2 | | 4(1-8)+10=-10 | | 2/1/2=1+1/4(x-2) | | 21/2=1+1/4(x-2) | | 0.05z+0.1(2z)+0.25(100-3z)=20 | | 7x-19=6x-19 | | 2x-8x-11=-6x+2-11 | | 3x+2=3x+2 | | 14-|-20|= | | (n^2-n-70)=0 | | -6x-16=3x+11 |

Equations solver categories